2001
DOI: 10.1111/j.1439-0507.2001.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral colonization by Candida spp. among AIDS household contacts

Abstract: Summary. This study was designed to investigate the oral yeast colonization rate of household contacts of AIDS patients. Sixty‐four AIDS household contacts were sequentially enrolled along with 103 HIV‐negative blood bank donors (control group). Samples were obtained by swabbing the oral mucosa. Yeast isolates were identified by classical methods and antifungal susceptibility testing was performed according to NCCLS microbroth assay. Candida spp. was recovered from the oral cavity of 33% of the AIDS household … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Candida spp. have been isolated from 40 to 60% of healthy mouths, whereas oral candidiasis is more common in immunodeficient individuals, those with severe underlying diseases, and upper denture wearers [3,4]. …”
Section: Introductionmentioning
confidence: 99%
“…Candida spp. have been isolated from 40 to 60% of healthy mouths, whereas oral candidiasis is more common in immunodeficient individuals, those with severe underlying diseases, and upper denture wearers [3,4]. …”
Section: Introductionmentioning
confidence: 99%
“…Further epidemiological studies for his environment, such as neighbors, classmates and relatives might be requested. Recently Milan and collaborators (12) reported that Candida spp. colonization was 33% of the AIDS household contacts in contrast with 14% of the HIV-negative control (11,12).…”
Section: Resultsmentioning
confidence: 99%
“…Recently Milan and collaborators (12) reported that Candida spp. colonization was 33% of the AIDS household contacts in contrast with 14% of the HIV-negative control (11,12). C. albicans was the most frequently isolated species.…”
Section: Resultsmentioning
confidence: 99%